Shikonin ameliorated mice colitis by inhibiting dimerization and tetramerization of PKM2 in macrophages - Huang, Baoyuan; Wang, Qiumei; Jiang, Lin; Lu, Shuru; Li, Chengcheng; Xu, Chunqi; Wang, Caiyan; Zhang, Enxin; Zhang, Xiaojun (Frontiers in Pharmacology, 2022)
Dysregulated immune response plays a pivotal role in Ulcerative colitis. In lamina propria of inflammatory colonic mucosa, macrophages tend to polarize into M1 type and metabolically reprogram to aerobic glycolysis. PKM2 orchestrates glucose metabolic switch in macrophages, which tetramer has high pyruvate kinase activity, while which dimer mainly works as a protein kinase to stabilize HIF-1α and mediate anabolism. Shikonin is a potent PKM2 inhibitor derived from traditional Chinese medicine Arnebiae Radix with anti-inflammatory and anticarcinogen activities. However, it is unclear which conformation of PKM2 is inhibited by Shikonin, and whether this inhibition mediates pharmacological effect of Shikonin. In this study, we examined the efficacy of Shikonin on dextran sulfate sodium-induced mice colitis and determined the states of PKM2 aggregation after Shikonin treatment. Results showed that Shikonin dose-dependently alleviated mice colitis, down-regulated expression of F4/80, iNOS and CD86, decreased IFN-γ, IL-1β, IL-6 and TNF-α, while increased IL-10 in mice colon. Furthermore, Shikonin suppressed the pyruvate and, lactate production and glucose consumptionproduction, inhibited the pyruvate kinase activity and nuclear translocation of PKM2, and decreased both dimerization and tetramerization of PKM2 in macrophages. In vitro assay revealed that Shikonin bounded to PKM2 protein, inhibited the formation of both dimer and tetramer, while promoted aggregation of PKM2 macromolecular polymer. TEPP-46, an activator of PKM2 tetramerization, attenuated the ameliorative effect of Shikonin on DSS mice. In summary, Shikonin improved mice colitis, which mechanism may be mediated by inhibiting dimerization and tetramerization of PKM2, suppressing aerobic glycolysis reprogram, improving mitochondrial dynamic, and therefore alleviating inflammatory response of macrophages.